Development and evaluation of an improved multiple frequency bioimpedance analyzer for disease management system / Sami Fathi Ali Khalil - Sami Fathi , Ali Khalil (2016)
This thesis presents the development of a novel multiple frequency bioimpedance analyzers (MFBIA). The analyzer is designed for diseases management, focusing on the management of dengue infection and the monitoring of high cholesterol level. The developed system consists of the hardware and the software modules. The advanced hardware (assembled in 8x4.5x2 cm box) measures the impedance parameters at 5 KHz, 50 KHz, 100 KHz and 200 KHz at the accuracy of 3.6 %, with an output current of 0.2 mA. The body composition prediction module was modeled from predefined equations using the data from 825 healthy Malaysian subjects. The diseases management system was developed based on the Bioimpedance Vector Analysis (BIVA) technique using data from 299 dengue patients and 339 high cholesterol elderly patients. The obtained results from the electrical testing showed maximum error at only 3.6% from the theoretical values. The validation using biological phantom presented significant correlations in estimating fat and fluid volumes using the developed MFBIA analyzer. The analysis of the equations showed that the Deurenberg’s model are the most appropriate method for the estimation of Fat-Free Mass, Fat Mass, Total Body Water, Extracellular Fluid and Intracellular Fluid as referenced to Dual Energy X-ray Absorptiometry. The investigation on the healthy subjects indicates significant correlation (Pearson’s correlation ≥ 0.8) between commercial analyzers and the developed MFBIA analyzer. The results from the BIVA analysis disclosed a significant vector shifting between the healthy and Dengue infected subjects (P<0.05) and the means impedance vector of normal and high cholesterol groups do differ significantly (P<0.05). In conclusion, a new MFBIA was designed and developed, and a novel diseases management system for dengue infection, and cholesterol level introduced.